PENGARUH SISTEM PENGENDALIAN INTERNAL, SISTEM KOMPENSASI, PERILAKU TIDAK ETIS, ASIMETRI INFORMASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Ni Made Tari Wahyuni; I Putu Deddy Samtika Putra (UNHI Press, 2022)
Accounting fraud is a form of fraud that is intentionally carried out which causes losses without being realized by the injured party and provides benefits for the perpetrators of fraud. This study aims to examine how the influence of the internal control system, compensation system, unethical behavior and information asymmetry on the tendency of accounting fraud. The population in this study were 15 Savings and Loan Cooperatives in Ubud District with 64 employees. The type of research used is quantitative and the sampling technique uses purposive sampling method, so that the sample obtained is 45 employees.The analytical method used in this research is multiple linear regression analysis. The hypothesis was tested using t-test with a significance level of 5%. Based on the results of the simultaneous analysis of the internal control system, compensation system, unethical behavior and information asymmetry, it has a positive and significant effect on auditor performance. Partially, the internal control system has a negative and significant effect on the tendency of accounting fraud, unethical behavior has a positive and significant effect on the tendency of accounting fraud. While the compensation system and information asymmetry have no effect on the tendency of accounting fraud.